Impacts of metabolic disruption, body mass index and inflammation on cognitive function in post-COVID-19 condition: a randomized controlled trial on vortioxetine - Kwan, Angela T.; Le, Gia H.; Guo, Ziji; Ceban, Felicia; Teopiz, Kayla M.; Rhee, Taeho G.; Ho, Roger; Di Vincenzo, Joshua D.; Badulescu, Sebastian; Meshkat, Shakila; Cao, Bing; Rosenblat, Joshua D.; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Post-COVID-19 Condition (PCC), as defined by the World Health Organization (WHO), currently lacks any regulatory-approved treatments and is characterized by persistent and debilitating cognitive impairment and mood symptoms. Additionally, metabolic dysfunction, chronic inflammation and the associated risks of elevated body mass index (BMI) have been reported. In this study, we aim to investigate the efficacy of vortioxetine in improving cognitive deficits in individuals with PCC, accounting for the interaction of metabolic dysfunction, elevated inflammation and BMI. Methods This is a post-hoc analysis of an 8-week randomized, double-blind, placebo-controlled trial that was conducted among adults aged 18 years and older living in Canada who were experiencing WHO-defined PCC symptoms. The recruitment of participants began in November 2021 and concluded in January 2023. A total of 200 individuals were enrolled, where 147 were randomized in a 1:1 ratio to receive either vortioxetine (5–20 mg, n = 73) or placebo (n = 74) for daily treatment under double-blind conditions. The primary outcome measure was the change in the Digit Symbol Substitution Test (DSST) score from baseline to endpoint. Results Our findings showed significant effects for time (χ2 = 7.771, p = 0.005), treatment (χ2 = 7.583, p = 0.006) and the treatment x time x CRP x TG-HDL x BMI interaction (χ2 = 11.967, p = 0.018) on cognitive function. Moreover, the between-group analysis showed a significant improvement with vortioxetine at endpoint (mean difference = 0.621, SEM = 0.313, p = 0.047). Conclusion Overall, vortioxetine demonstrated significant improvements in cognitive deficits among individuals with baseline markers of metabolic dysfunction, elevated inflammation and higher BMI at endpoint as compared to placebo. Trial Registration NCT05047952 (ClinicalTrials.gov; Registration Date: September 17, 2021).